2007
DOI: 10.1007/s11663-006-9016-z
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Zirconium Metal by the Electrochemical Reduction of Zirconium Oxide

Abstract: An electrolytic production technique based on the electrochemical reduction of zirconium oxide was developed. Various factors affecting the reduction process were investigated. These factors include the cell voltage, the electrolysis time, the composition of the molten bath, and the temperature of the bath. The novel cell design succeeded in the production of zirconium powder or sponge with less than 400 ppm oxygen in a semicontinuous manner.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
38
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(41 citation statements)
references
References 20 publications
0
38
0
1
Order By: Relevance
“…By the Fray-Farthing-Chen (FFC) Cambridge process, Ti, [6] Cr, [7] Si, [8] Cu, [9] Al, B, Fe, V, Nb, U, Nd, Zr, Hf, Ce, and Ni [10][11][12][13] have already been produced in laboratory experiments. In addition, Dring et al [14] and Bhagat et al [15] have reported that Ti-W alloys were produced via electrochemical reduction of TiO 2 -WO 3 mixed oxide preforms in molten calcium chloride electrolyte at 1173 K (900°C).…”
Section: Introductionmentioning
confidence: 99%
“…By the Fray-Farthing-Chen (FFC) Cambridge process, Ti, [6] Cr, [7] Si, [8] Cu, [9] Al, B, Fe, V, Nb, U, Nd, Zr, Hf, Ce, and Ni [10][11][12][13] have already been produced in laboratory experiments. In addition, Dring et al [14] and Bhagat et al [15] have reported that Ti-W alloys were produced via electrochemical reduction of TiO 2 -WO 3 mixed oxide preforms in molten calcium chloride electrolyte at 1173 K (900°C).…”
Section: Introductionmentioning
confidence: 99%
“…An electrochemical process that is capable of producing zirconium metal in a consolidated form and that is also devoid of the problems associated with the metallothermic reduction is, hence, desirable. AbdelKader et al [8] reported a process for reducing zirconium dioxide powder in the presence of electrochemically produced calcium metal in a molten calcium chloride medium. Another possibility is the electrodeoxidation of solid zirconium dioxide in molten salt medium, which is reported in this article.…”
Section: Introductionmentioning
confidence: 99%
“…The amount of salt used in the process maybe small because oxide ions don't accumulate in the salt bath [7]. The simple electrochemical process attracted worldwide attention and significant efforts have been made since then to study and develop the process for production of many metals/alloys from their oxides, for example, electrochemical reduction of ZrO2 [8], HfO2 and niobia-doped HfO2 [9], CeO2 [10], V2O5 [11], Cr2O3 [12], UO2 [13], Fe2O3 [14], Ta2O5 [15], UO2-PuO2 mixed oxides [16], Al2O3 [17], SiO2 [18,19], WO2 [20] and the production of Ti-Mo alloys [21], Ti-W alloys [22], TiFe Alloys [23], NiTi [24], NbSi alloys [25] and so on.…”
Section: Introductionmentioning
confidence: 99%